An autosomal dominant syndrome of acromegaloid facial appearance and generalised hypertrichosis terminalis. Issue 11 (November 1996) - Irvine, A D; Dolan, O M; Hadden, D R; Stewart, F J; Bingham, E A; Nevin, N C
Abstract : We report a family in which a phenotype of acromegaloid facial appearance (AFA) and generalised hypertrichosis terminalis segregates through three generations. Congenital hypertrichosis terminalis and AFA have been previously reported as independent autosomal dominant traits. This is the first report to delineate an autosomal dominant transmission of the combined phenotype.